Implementasi dan Pemanfaatan Teknologi Digital untuk Meningkatkan Brand Awareness pada Produk Skincare di Indonesia - Elli Sulistyaningsih; Sugeng Siswanto (Universitas Borobudur, 2023)
The creative economy sector is one of the sectors that is growing in Indonesia. Not only does it make a real contribution to national economic growth, this sector is also one of the main drivers in building the image and brand awareness of a product. To achieve this, the use of social media is an important key in introducing and expanding market reach. With the increasing number of social media users, the creative economy sector can utilize social media to increase brand awareness and expand market reach. The implementation of digital technology in increasing brand awareness in the creative economy sector is also followed by measurement and data analysis. This study used quantitative methods with multiple regression analysis techniques, and data analysis tools used the SPSS version 25 program. Based on the results of the regression analysis, it was found that the significance value of the influence of digital technology on increasing brand awareness was 0.001, because the sig. < 0.05 and a positive regression coefficient of 846,715, it is concluded that digital technology has a positive and significant effect on increasing brand awareness, meaning that the better the digital technology, the higher the increase in brand value.